Genome-Wide Association Study of Bone Mineral Density in Korean Men - Ye Seul Bae; Sun-Wha Im; Mi So Kang; Jin Hee Kim; Soon Hang Lee; Be Long Cho; Jin Ho Park; You-Seon Nam; Ho-Young Son; San Deok Yang; Joohon Sung; Kwang Ho Oh; et al. (Genomics & Informatics, 2016)
Osteoporosis is a medical condition of global concern, with increasing incidence in both sexes. Bone mineral density (BMD), a highly heritable trait, has been proven a useful diagnostic factor in predicting fracture. Because medical information is lacking about male osteoporotic genetics, we conducted a genome-wide association study of BMD in Korean men. With 1,176 participants, we analyzed 4,414,664 single nucleotide polymorphisms (SNPs) after genomic imputation, and identified five SNPs and three loci correlated with bone density and strength. Multivariate linear regression models were applied to adjust for age and body mass index interference. Rs17124500 (p = 6.42 × 10-7), rs34594869 (p = 6.53 × 10-7) and rs17124504 (p = 6.53 × 10-7) in 14q31.3 and rs140155614 (p = 8.64 × 10-7) in 15q25.1 were significantly associated with lumbar spine BMD (LS-BMD), while rs111822233 (p = 6.35 × 10-7) was linked with the femur total BMD (FT-BMD). Additionally, we analyzed the relationship between BMD and five genes previously identified in Korean men. Rs61382873 (p = 0.0009) in LRP5, rs9567003 (p = 0.0033) in TNFSF11 and rs9935828 (p = 0.0248) in FOXL1 were observed for LS-BMD. Furthermore, rs33997547 (p = 0.0057) in ZBTB and rs1664496 (p = 0.0012) in MEF2C were found to influence FT-BMD and rs61769193 (p = 0.0114) in ZBTB to influence femur neck BMD. We identified five SNPs and three genomic regions, associated with BMD. The significance of our results lies in the discovery of new loci, while also affirming a previously significant locus, as potential osteoporotic factors in the Korean male population.